Computational modelling of T-joint fillet welding - Fernandes, F. A. O. (2021)
The last decade has been rich in advances and progress in the field of Computational Welding Mechanics. Numerical algorithms made it possible to assess complex phenomena such as the residual stresses and distortions originated during welding. Currently, software specifically designed for welding simulation is being introduced, capable of analysing thermo-metallurgical and thermo-mechanical phenomena typical of any welding process and necessary to build reliable models. This work focuses on the development of a numerical model under Abaqus code. Although not developed specifically for welding applications, it is a powerful software here assessed to simulate the welding of fillet T-joints. A benchmark test, based on T-joint fillet welding of S355JR steel, is simulated and comparisons are performed with the experiments and other numerical models developed under Abaqus FE code. For this benchmark, the thermomechanical model was developed to simulate the pass of double joints, each followed by cooling periods. Based on previous works available in the literature, the influence of the element type is assessed, and different techniques of element birth and death employed to simulate the weld bead deposition are also explored. In addition, the torch temperature ramping is also analysed. Thanks to the temperature field and residual distortions data from the experiments, it was possible to assess the numerical model reliability. The results show a reasonable agreement between the numerical model and the experiments.